Significance of Collaborative Learning Guidelines in 21st Century Education on Functional Limits Material in Madrasah Tsanawiyah - Zahroh, Umy; Rachmawati, Nadiya Itsnaini; Darmayanti, Rani (CV. BImbingan Belajar Assyfa, 2023)
Collaboration skills are critical for students, offering a pathway to increased knowledge, social interaction, self-confidence, and motivation. This research aims to improve students' collaborative skills in mathematics learning, especially in function limit material at Madrasah Tsanawiyah. Using a literature review approach in 3 international databases covering 2015-2023, this research explores various relevant collaborative learning guidelines in 21st-century education. The methods used include descriptive analysis of existing literature and quantitative evaluation of previous research results by identifying studies focusing on implementation in various countries, including Indonesia. The research results show that collaborative learning can significantly improve students' understanding of function limits through quantitative data that supports this claim. In addition, active involvement in group discussions and joint problem-solving has increased student motivation and self-confidence. The problem-based learning model has emerged as a practical approach to developing these collaborative skills. This research provides critical insight into the importance of collaborative learning strategies in the mathematics curriculum at Madrasah Tsanawiyah, focusing on function limits material. These findings highlight the vital role of collaboration-based learning in preparing students to face the challenges of the 21st century, both in academic contexts and everyday life. Limitations of this study include the lack of longitudinal data and wider sample variation. Future research should incorporate mixed research methods to explore the impact of problem-based learning models further.